2020
DOI: 10.1155/2020/7825943
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Potential of Lactic Acid Starter Cultures Isolated from a Traditional Fermented Sorghum-Millet Beverage

Abstract: The purpose of this study was to establish the probiotic potential of lactic acid bacteria (LAB) starter cultures, Lb. plantarum MNC 21, L. lactis MNC 24, and W. confusa MNC 20, isolated from a traditionally fermented sorghum-millet beverage from Uganda. The cultures were examined for tolerance to acid and bile salts, bile salt hydrolase (BSH) activity, antibiotic susceptibility, biogenic amine production, mucin degradation, hydrophobicity, auto-aggregation, adherence to the ileum, coaggregation, and antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…The tolerance of some of the isolated strains (including PB2) to acidity and bile salt is vital for bacterial survival and growth in the gastro-intestinal tract. These attributes are the main requirements for bacteria to be considered probiotics [ 44 , 45 ]. Tolerance to bile salts is a prerequisite for colonization and metabolic activity of bacteria in the small intestine of the host [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance of some of the isolated strains (including PB2) to acidity and bile salt is vital for bacterial survival and growth in the gastro-intestinal tract. These attributes are the main requirements for bacteria to be considered probiotics [ 44 , 45 ]. Tolerance to bile salts is a prerequisite for colonization and metabolic activity of bacteria in the small intestine of the host [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on criterions used to define a probiotic organism, putative probiotic strains should be screened for their functional characteristics (persistence in the gastrointestinal tract, resistance to gastric acidity and bile salts, antimicrobial activity against pathogenic, and adhesion to epithelial cells) and safety properties such as non-pathogenicity and antibiotic resistance characteristics (Byakika et al, 2020). Selection process of probiotic micro-organisms probiotics, must be extended to other criteria such as prevent intestinal disorders, promote antagonistic and antimutagenic properties, improve the immune system and involvement in disease prevention and/or treatment (Abouloifa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that 0.3% (w/v) bile salt concentration in the human gut also varies according to diet and the level of pancreatic enzyme secretion ( 33 ). Succi et al ( 34 ) also reported that most of the LAB showed resistance to a 0.5% bile concentration, and Byakika et al ( 35 ) examined whether the probiotic bacteria were tolerant to 1% bile salt. Hsieh et al ( 32 ) also reported that 0.3% bile was used for a bile tolerance test and Lactobacillus TSR332 exhibited the highest viability (4.74x10 8 CFU/ml) indicating high tolerance to bile salt.…”
Section: Discussionmentioning
confidence: 99%
“…Rashmi and Gayathri ( 13 ) investigated whether gluten-hydrolyzing bacteria adhered to the Caco-2 cell line and inhibited cell invasion by E. coli and L. monocytogenes . Byakika et al ( 35 ) used the goat ileum to assess cell adhesion, and Behbahani et al ( 37 ) used scanning electron microscopy to identify that the adhesion level of the L. plantarum strain L15 to Caco-2 cells was 12%. Aissi et al ( 24 ) employed HT-29, Caco-2 and INT-407 cells, as well as Bifidobacterial strains, and microscopically studied them.…”
Section: Discussionmentioning
confidence: 99%